MRI technique for the preoperative evaluation of deep infiltrating endometriosis: current status and protocol recommendation. Issue 3 (March 2016) - Schneider, C.; Oehmke, F.; Tinneberg, H.-R.; Krombach, G.A.
Abstract : Endometriosis is a common cause of chronic pelvic pain and infertility. It is defined as the occurrence of endometrial tissue outside the uterine cavity and can manifest as a peritoneal, ovarian or infiltrating form, the latter being referred to as deep infiltrating endometriosis (DIE). Surgery is essential in the treatment of DIE and depending on the severity of the disease, surgery can be difficult and extensive. Beside clinical examination and ultrasound, magnetic resonance imaging (MRI) has proven its value to provide useful information for planning surgery in patients with suspected DIE. To optimise the quality of MRI examinations, radiologists have to be familiar with the capabilities and also the limitations of this technique with respect to the assessment of DIE. MRI yields morphological information by using mainly T1- and T2-weighted sequences, but can also provide functional information by means of intravenous gadolinium, diffusion-weighted imaging or cine-MRI. In this article, these techniques and also adequate measures of patient preparation, which are indispensable for successful MRI imaging for the preoperative evaluation of DIE, are reviewed and a comprehensive protocol recommendation is provided.